A family of constacyclic codes over 𝔽pm [υ, w]/⟨υ2 − 1, w2 − 1, υw − wυ⟩. (13th October 2020) - Islam, Habibul; Verma, Ram Krishna; Prakash, Om
In this article, for any odd prime p, we study the constacyclic and skew constacyclic codes of arbitrary length over R = 𝔽 p m [ υ, w ]/⟨ υ 2 − 1, w 2 − 1, υw − wυ ⟩. It is shown that the Gray images of constacyclic and skew constacyclic codes of length n over R are quasi-twisted and skew quasi-twisted codes, respectively over 𝔽 p m of length 4 n with index 4. Also, the structures of constacyclic and skew constacyclic codes are obtained by decomposition method.